2017
DOI: 10.1038/s41598-017-10134-2
|View full text |Cite|
|
Sign up to set email alerts
|

The Oncogenic Role of COL23A1 in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common adult renal neoplasm and its incidence continues to increase. Collagen is the most abundant extracellular matrix protein in stroma, and contributes to the development and progression of ccRCC. We examined the human collagen type XXIII α1 chain (COL23A1) expression in ccRCC and the relationship between COL23A1 and patients’ survival. We found COL23A1 mRNA was elevated in tumor compared with adjacent normal tissues, which was further validated by TCGA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Furthermore, it was indicated that the high-risk group was markedly associated with renal cell carcinoma, bladder cancer and small cell lung cancer. These results were consistent with previous studies that collagen gene expression was correlated with the poor prognosis of those cancers (Koskimaki et al, 2010; Wan et al, 2015; Xu et al, 2017; Zeng et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it was indicated that the high-risk group was markedly associated with renal cell carcinoma, bladder cancer and small cell lung cancer. These results were consistent with previous studies that collagen gene expression was correlated with the poor prognosis of those cancers (Koskimaki et al, 2010; Wan et al, 2015; Xu et al, 2017; Zeng et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Clear cell renal cell carcinoma (ccRCC) is the most common subtype of RCC ( 15 ). A study at our center demonstrated that 88.9% of RCC patients have a clear cell subtype in coastal Chinese areas, consistent with results (87.4%) from the SEER (2004–2012) database ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that ccRCC patients have more malignant characteristics and worse prognosis. Further advancements are thus urgently required for ccRCC diagnosis and treatment ( 15 ). In our study, we focused on prognosis prediction for stage III ccRCC patients and constructed a nine-gene signature, using data from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases.…”
Section: Introductionmentioning
confidence: 99%
“…22 Silencing type 23 collagen in lung cancer and clear cell renal cell lines showed altered adhesion protein expressions and less ability on cell adhesion and migration. 22,23 However, type 23 collagen is also present in other tissues, and the function and use in other diseases are yet unknown. To our knowledge, this is the first study showing that type 23 collagen level is modulated in IBD.…”
Section: Discussionmentioning
confidence: 99%